The use of the Internet as a socialization tool in adults with cerebral palsy in Brazil - Curioso-Vilchez, Ivan Carlos [UNESP] (Centro Espanol Documentacion Discapacidad-cedd, 2021)
The research studies of use of the Internet for socialization by people with physical disabilities such as adults with cerebral palsy are insufficient. In this paper, the author identifies the potential of this technology as a tool for socialization. Twelve adults with cerebral palsy were asked questions by using semi-structured interviews in the State of Sao Paulo, Brazil. Five thematic categories of analysis were suggested from the analysis and the interview transcripts. First category was related to the use of the Internet to maintain and expand interpersonal relationships. Second category was associated to the benefits of the Internet as an emotional well-being tool to fight critical situations. Third category was related to social visibility of their condition that helps to show who they are. Fourth category was related to the political participation where they can express their points of views and can have their legal rights. The final category was related to the attitudinal barriers that people without disabilities associate when this population group uses the Internet. In conclusion, the use of the Internet has a positive impact in inclusion and participation of adults with cerebral palsy by expanding their possibilities to promote their social and political participation.
Keywords: Inclusive education; socialization; digital technologies; Internet; adults; physical disability; cerebral palsy